Concise Review: CXCR4/CXCL12 Signaling in Immature Hematopoiesis—Lessons From Pharmacological and Genetic Models. (25th May 2015) - Karpova, Darja; Bonig, Halvard
Abstract: Dominant, although nonexclusive roles of CXCR4 and its chief ligand CXCL12 in bone marrow (BM) retention and preservation of the relative quiescence of hematopoietic stem/progenitor cells (HSPCs), along with their involvement in human immunodeficiency virus infection, in trafficking of mature hematopoietic cells to sites of inflammation and in orderly migration of nonhematopoietic cells during embryogenesis, explain the significant interest of the scientific community in the mode of action of this receptor–ligand pair. In this focused review, we seek to distil from the large body of information that has become available over the years some of the key findings about the role of CXCR4/CXCL12 in normal immature hematopoiesis. It is hoped that understanding the mechanistic insights gained there from will help generate hypotheses about potential avenues in which cancer/leukemia cell behavior can be modified by interference with this pathway. Stem Cells   2015;33:2391–2399